Fuzzy linear regression models with least square errors - Modarres, M.; Nasrabadi, E.; Nasrabadi, M.M. (Applied mathematics and computation, 2005)
To estimate the parameters of fuzzy linear regression models with fuzzy output and crisp inputs, we develop a mathematical programming model in this paper. The method is constructed on the basis of minimizing the square of the total difference between observed and estimated spread values or in other words minimizing the least square errors. The advantage of the proposed approach is its simplicity in programming and computation as well as its performance. To compare the performance of the proposed approach with the other methods, two examples are presented.